Effect of Calcination Temperature on The Structure and Catalytic Performance of ZrO2 Catalyst in Phenol Degradation - Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier Ltd., 2019)
In this study, tetragonal electrogenerated zirconia nanoparticles (t-EGZrO2) was prepared via simple electrochemical method, and stabilized at a lower calcination temperature without the addition of a dopant in the preparation step. The use of tetraethylammonium perchlorate (TEAP) in the electrolysis system was responsible for the stabilization of t-EGZrO2 by preventing the agglomeration of metal clusters with undesired powders, subsequently decrease in ZrO2 crystal size. The photoactivity of the catalyst was subjected to the degradation of phenol in an aqueous solution. This resulted in 98 degradation of 10 mg/L phenol solution using 0.4 mg/L of catalyst dosage at pH 9 under light irradiation within 1 hour of contact time. The comparison studies were also conducted using monoclinic electrogenerated zirconia (m-EGZrO2), commercial zirconia (c-ZrO2), and photolysis as a control experiment, which gives 45, 78, and 3, respectively. Good photoactivity of t-EGZrO2 toward phenol degradation with simple operation of the system exhibits great potential for improving the quality of wastewater discharge from industries.